2019
DOI: 10.1017/jfm.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction and instabilities of flows in longitudinally grooved annuli

Abstract: The primary and secondary laminar flows in annuli with longitudinal grooves and driven by pressure gradients have been analysed. There exist geometric configurations reducing pressure losses in primary flows in spite of an increase of the wall wetted area. The parameter ranges when such flows exist have been determined using linear stability theory. Two types of secondary flows have been identified. The first type has the form of the classical travelling waves driven by shear and modified by the grooves. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Before moving further, note that, for the sake of completeness of our analysis, the order of the inertial terms (including the neglected nonlinear terms) in (3.19) is evaluated in § 2 of the online supplementary material. Also note that the analysis and treatment of the inertial terms in our work are consistent with those in previous studies (Moradi & Floryan 2016, 2019; Jiao & Floryan 2021), which have solved their problem for the base flow at large Reynolds numbers and, similar to our work, they have obtained converged results.…”
Section: Semi-analytical Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…Before moving further, note that, for the sake of completeness of our analysis, the order of the inertial terms (including the neglected nonlinear terms) in (3.19) is evaluated in § 2 of the online supplementary material. Also note that the analysis and treatment of the inertial terms in our work are consistent with those in previous studies (Moradi & Floryan 2016, 2019; Jiao & Floryan 2021), which have solved their problem for the base flow at large Reynolds numbers and, similar to our work, they have obtained converged results.…”
Section: Semi-analytical Modelsupporting
confidence: 90%
“…In this flow, with periodic positioning of the rectangular trenches, the authors have used the Floquet–Bloch theory to be able to examine the disturbances with wavelengths larger than that of the trenches. In some other studies, the researchers have solved for the inertial flow in confined geometries with periodic groovy walls, followed by flow stability analysis (Floryan 2005; Szumbarski 2007; Moradi & Floryan 2016, 2019).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…When fluid flows over a surface, the characteristics of the surface itself can play a significant role in the flow dynamics. Even small-scale features on the surface can result in major alterations on the flow physics. For instance, inspired by properties of biosurfaces, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the number of possible surface patterns is limitless, here we focus on the regular wall roughness in the form of longitudinal grooves positioned such that ridges of the geometry run parallel to the flow direction, as schematically illustrated in figure 1. This type of grooves has been investigated as a means to manipulate flow dynamics in a doubly periodic grooved channel (Szumbarski 2007; Mohammadi & Floryan 2014; Mohammadi, Moradi & Floryan 2015; Yadav, Gepner & Szumbarski 2017; Gepner & Floryan 2020; Gepner, Yadav & Szumbarski 2020), singly periodic corrugated duct (Yadav, Gepner & Szumbarski 2018; Pushenko & Gepner 2021) and grooved, annular (Moradi & Floryan 2019; Moradi & Tavoularis 2019) configurations. It has been shown that properly shaped longitudinal grooves lead to a reduction of hydraulic drag (Szumbarski & Błoński 2011; Szumbarski, Blonski & Kowalewski 2011; Mohammadi & Floryan 2015; Ng, Jaiman & Lim 2018; Moradi & Floryan 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This type of grooves has been investigated as a means to manipulate flow dynamics in a doubly periodic grooved channel (Szumbarski 2007; Mohammadi & Floryan 2014; Mohammadi, Moradi & Floryan 2015; Yadav, Gepner & Szumbarski 2017; Gepner & Floryan 2020; Gepner, Yadav & Szumbarski 2020), singly periodic corrugated duct (Yadav, Gepner & Szumbarski 2018; Pushenko & Gepner 2021) and grooved, annular (Moradi & Floryan 2019; Moradi & Tavoularis 2019) configurations. It has been shown that properly shaped longitudinal grooves lead to a reduction of hydraulic drag (Szumbarski & Błoński 2011; Szumbarski, Blonski & Kowalewski 2011; Mohammadi & Floryan 2015; Ng, Jaiman & Lim 2018; Moradi & Floryan 2019). Interestingly, there are indications, both experimental (Kim & Hidrovo 2012; Bolognesi, Cottin-Bizonne & Pirat 2014) and theoretical (Crowdy 2017), that drag reduction, attributed to the superhydrophobic effect, could, at least in some cases, be related to drag reduction reported for flows through longitudinally patterned geometries, such as those considered here.…”
Section: Introductionmentioning
confidence: 99%